Free Trade and Sailors' Rights in the War of 1812. - Gilje, Paul A. (Cambridge University Press, 2013)
Examines the slogan 'free trade and sailors rights', tracing its sources to eighteenth-century thought and Americans' experience with impressment into the British navy.